2019
DOI: 10.3389/fmicb.2019.01292
|View full text |Cite
|
Sign up to set email alerts
|

Diet Control More Intensively Disturbs Gut Microbiota Than Genetic Background in Wild Type and ob/ob Mice

Abstract: Changes in environmental and genetic factors are vital to development of obesity and its complications. Induction of obesity and type 2 diabetes by both leptin deficiency (ob/ob) and high fat diet (HFD) has been verified in animal models. In the present experiment, three types of diets (normal diet; ND, HFD and high sucrose diet; HSD) and two types of genetic mice (Wild type: WT and ob/ob) were used to explore the relationship among diet supplements, gut microbiota, host genetics and metabolic status. HFD incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Microbiome analysis has revealed that disease progression is associated with changes in the fecal microbiome. Research on animal models has indicated that different responses based on host genotypes may contribute to the development of metabolic disorder phenotypes linked with gut microbiota alterations (Miranda-Ribera et al, 2019 ; Wang J. H. et al, 2019 ). In healthy individuals, most intestinal bacteria can be classified under five phyla, Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria , and Verrucomicrobia (Tremaroli and Backhed, 2012 ).…”
Section: Host Gut Microbiota and T2dm: Pathogenesismentioning
confidence: 99%
“…Microbiome analysis has revealed that disease progression is associated with changes in the fecal microbiome. Research on animal models has indicated that different responses based on host genotypes may contribute to the development of metabolic disorder phenotypes linked with gut microbiota alterations (Miranda-Ribera et al, 2019 ; Wang J. H. et al, 2019 ). In healthy individuals, most intestinal bacteria can be classified under five phyla, Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria , and Verrucomicrobia (Tremaroli and Backhed, 2012 ).…”
Section: Host Gut Microbiota and T2dm: Pathogenesismentioning
confidence: 99%
“…Indeed, it has been known for a long time that ob/ob mice display high retention of nutrient-derived energy, which is further enhanced by consumption of HFD [14]. HFD induction of adiposity is associated with a proportional increase of plasma leptin levels which do not result in decreased caloric consumption, witnessing the development of a leptin resistance, whereas feeding of HFD to ob/ob mice is accompanied by even further increase of their total food intake [15,16].Thus, in the present study, we used HFD to exacerbate obesity in hyperphagic ob/ob mice and then treated them chronically with H. alvei HA4597™, to compare its effects with untreated mice. We also compared the anti-obesity effects of H. alvei with the drug orlistat, a lipase inhibitor used in humans for body weight control.…”
mentioning
confidence: 99%
“…Indeed, it has been known for a long time that ob/ob mice display high retention of nutrient-derived energy, which is further enhanced by consumption of HFD [14]. HFD induction of adiposity is associated with a proportional increase of plasma leptin levels which do not result in decreased caloric consumption, witnessing the development of a leptin resistance, whereas feeding of HFD to ob/ob mice is accompanied by even further increase of their total food intake [15,16].…”
mentioning
confidence: 99%
“…57 Together, these results support the roles for the Firmicutes to Bacteroidetes abundance ratio and diversity metrics as a potential descriptive biomarkers of obesity. 50,58 In the laboratory, many of the physiological changes related to variations in the circannual rhythm can be achieved by manipulating the length of the day, making it an ideal model. Yet, very limited studies have assessed the effect of the duration of the day on the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have also been observed in models of induced obesity and type 2 diabetes using the leptin-deficient mouse (ob/ob) as well as high-fat diet. 58 Therefore, the findings that were revealed via machine learning may be helpful when predicting potential metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%